Study on the relationship between berry, grape, red wine consumption and cognitive impairment in middle-aged and elderly people in China - Jiang, Xinting; Chen, Meirong; Cui, Liang; Guo, Qihao; Huang, Lin (Frontiers in Nutrition, 2024)
Some evidence suggests that fruit and alcohol consumption may be related to cognitive impairment. This study conducted a cross-sectional study on the " correlation between eating habits and cognitive function of the middle-aged and elderly population in China". The purpose of this study is to explore the relationship between fruit consumption, drinking habits and cognitive impairment in Chinese people over 50 years old. The results show that the protective factors of cognitive impairment are the preference for berries and the daily intake of 100-200g grapes in Chinese middle-aged and elderly people with objective cognitive unimpaired. The habit of drinking red wine is a protective factor for cognitive impairment in Chinese middle-aged and elderly people with mild cognitive impairment (MCI). However, this study did not find the relationship between white wine, beer, yellow rice wine, liquor and cognitive impairment.Therefore, we believe that berries, grapes and red wine consumption can protect the cognitive function of the middle-aged and elderly people in China, and the protective function is related to the basic cognitive state.With the rapid growth of the elderly population in China, the prevalence of dementia such as Alzheimer's disease(AD) has also increased in the past few decades [1 ] . Cognitive decline is currently believed to be the most common cause of dementia [2 ] . The focus of clinical and medical research is on the diagnosis and treatment of early clinical cognitive impairment [3 ] .Recent studies have found that healthy eating patterns are associated with a lower risk of cognitive impairment among the elderly in China [4 ] .